PENINGKATAN PENGETAHUAN SANTRIWATI DALAM MENJAGA KESEHATAN REPRODUKSI WANITA - Sri Rahayu; Emma Rachmawati; Mulyanti Mulyanti; Rina Yuliana Subur (Bajang Institute, 2023)
Al-Husna Islamic Boarding School, Bogor Regency, which consists of young women (santriwati) with limited health service infrastructure, there has never been a visit by local health workers who provide counseling on women's reproductive health, toilet cleanliness, food intake, hygiene behavior, and problems with femininity that are often experienced by female students. These factors in the future will become an accumulation (time bomb) of disturbances in the reproductive organs, physically and mentally in female students. The community service activity was themed